Boost Your Digital Portfolio: From Linkedin Profile to Github Repository - Fizar, Bintang Al; Fakhul Jannah, Elsa Ananda Hanifah; Zahro, Rahmita; Vivria, Muhammad Efendi; Sutrisno, Mirza; Adharani, Yana; Mujiastuti, Rully; Rosanti, Nurvelly (Edumedia Solution, 2025)
In the modern era, having a digital portfolio is an important requirement for students and aspiring professionals in the field of technology. To support this, LinkedIn profile management and project publication to GitHub are strategies that can be applied. The activity themed